Integrated Services to Fight Maternal Mortality in Nicaragua - Ruiz Abril, Maria Elena; Fernandez Díaz, Jesus María (World Bank, Washington, DC, 2012)
Reducing Nicaragua's high maternal mortality rate of 150 maternal deaths per 100,000 live births is a priority in the Government's Health Plan and Poverty Reduction Strategy. Efforts to improve reproductive health face many challenges. Adolescent pregnancy rates are among the highest in the region (130 per 1,000 15-19 year olds). Fertility in rural areas (5.4 children per woman) and among poor women (6.6) is significantly higher than the Latin American average of 2.8 children per woman. Poverty, limited educational and employment opportunities, traditional gender roles and disempowerment of women, and poor access to distant health services across difficult terrain in remote rural areas are significant barriers. Maternal complications need immediate attention, are difficult to manage and often lead to the death of the woman (and/or child).